The Women's Tennis Association and media framing of the 2018 U.S. Open Final - Police, Chelsea; Hambrick, Marion E. (London : SAGE Publications: SAGE Business Cases Originals, 2020)
Sports organizations attempt to generate positive news coverage for their events and athletes. Journalists and other media providers engage in media framing when they select certain news stories to produce and promote, highlighting their relative salience. This occurred with the news coverage of the 2018 U.S. Open final match between Serena Williams and Naomi Osaka, two star athletes governed by the Women's Tennis Association. Media providers offered an array of stories, many of which focused on the altercation between Williams and the match officials rather than Osaka winning her first Grand Slam. The case study provides an overview of the Women's Tennis Association and this news coverage, offers a discussion of media framing, and asks readers to assess the effects of media choices when discussing athletes and events and the business implications for sports organizations making these media decisions.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Women's Tennis Association -- Case studies; Tennis -- Tournaments -- Press coverage -- Case studies; U.S. Open Final -- Press coverage -- Case studies